The role of goats in improving crop substrate: Post-ingestion germination and survival of two Mediterranean herbaceous forage species - Mancilla-Leytón J.M.; Martín Vicente A. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
We assessed the ability of Payoya goats to disperse two endozoochorous Mediterranean herbaceous forage species: Trifolium subterraneum (legume) and Lolium rigidum (grass). Seeds of these two species were fed to six individually housed goats. For five days following ingestion, the faeces were collected every 24 hours. Following examination of the contents of the faeces the percentage of seed loss (chewing and digestion) was determined as well as the distribution of seed recovery over time, germination efficacy and survival of seedlings after passage through the digestive tract. The percentage of seeds recovered was 1.5 percent in T. subterraneum and 2 percent in L. rigidum, whilst germination was between 33-38 percent in T. subterraneum and 35-37 percent in L. rigidum. In the study species, biomass and herbage height was clearly higher in the seedlings emerged from the faeces than in controls. Despite the low values obtained, we can consider that the use of livestock can be a cheap and effective method to introduce new pasture species.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)